Aims of Philosophy and Problems of Its Teaching - Nekrašas, Evaldas (Problemos, 1990)
In the paper the historical standpoints, concerning the origin and the aims of philosophy as well as the problems facing the Marxist philosophy today are considered. The critical analysis of society and its culture is claimed to be a fundamental task of philosophy. Nevertheless, in the end of 1920th the social philosophy in the U.S.S.R. has lost its critical character. It is argued that the metamorphosis was conditioned not only by political circumstances, but by the philosophical attitudes leading to the objectivistic interpretation of history as well. The critical character of the Marxist philosophy means that in its teaching the most attention should be paid to the development of the habit of autonomous and critical thinking. The latter target is attainable only when the philosophy is taught problematically. Some aspects of the problematic teaching of philosophy are considered and practical recommendations of its improvement are given.